(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Strong attacks of Scatella stagnalis Fallén (Diptera Ephydridae) are discovered on horticultural crops and flowers under greenhouse, in Latina province. The particular structure of labella of the mouth-parts allows adults to damage the tender crop tissues, which finally tend to dry up. Pullulations of the insect are favoured by the presence, in proximity of crops, of cisterns or artificial basins for collection of water for irrigation, where the decaying vegetation makes possible an extraordinary growth of larvae. Besides morphological caracteristics of pest lips are explained and some remarks are made on the possibilities of control.